Virtual reality interventions to improve function after stroke - Pereira, Miguel (2024)
Stroke is the most common neurological disease and one of the most common fatal diseases in the world. Stroke patients suffer from several physical, cognitive, and sensory complications that impact their functionality and independence in daily activities and, consequently, can reduce their quality of life. Given this impact, it is important to assess the various ways to ensure effective and satisfactory rehabilitation for the stroke person. Virtual reality has been proven in recent times as a promising tool in stroke motor rehabilitation, being effective with its immersive elements and, at the same time, motivating patients. With all this in mind, this chapter aimed to analyze the current scientific evidence of Virtual Reality intervention for functional rehabilitation of stroke patients.